2014
DOI: 10.1186/1471-2318-14-95
|View full text |Cite
|
Sign up to set email alerts
|

Emergency ambulance service involvement with residential care homes in the support of older people with dementia: an observational study

Abstract: BackgroundOlder people resident in care homes have a limited life expectancy and approximately two-thirds have limited mental capacity. Despite initiatives to reduce unplanned hospital admissions for this population, little is known about the involvement of emergency services in supporting residents in these settings.MethodsThis paper reports on a longitudinal study that tracked the involvement of emergency ambulance personnel in the support of older people with dementia, resident in care homes with no on-site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 16 publications
(17 reference statements)
0
35
0
Order By: Relevance
“…Eleven of these 13 studies accounted for need (Amador et al, ; Bardsley et al, ; Blackburn, Locher, & Kilgore, ; Carter, ; Chappell, Dlitt, Hollander, Miller, & McWilliam, ; Deraas, ; Gruneir et al, ; Hollander & Chappell, ; Hutt et al, ; Sloane et al, ; Wysocki et al, ) and a further two did so in a subset of the reported analyses (Reeves & Baker, ; Victor, Healy, Thomas, & Seargeant, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eleven of these 13 studies accounted for need (Amador et al, ; Bardsley et al, ; Blackburn, Locher, & Kilgore, ; Carter, ; Chappell, Dlitt, Hollander, Miller, & McWilliam, ; Deraas, ; Gruneir et al, ; Hollander & Chappell, ; Hutt et al, ; Sloane et al, ; Wysocki et al, ) and a further two did so in a subset of the reported analyses (Reeves & Baker, ; Victor, Healy, Thomas, & Seargeant, ).…”
Section: Resultsmentioning
confidence: 99%
“…Across included studies, social care utilisation was operationalised as: the amount of social care used (six studies, Table ) (Amador et al, ; Carter, ; Deraas, ; Gruneir et al, ; Hutt et al, ; Reeves & Baker, ); the type of social care used (four studies, Table ) (Bardsley et al, ; Chappell et al, ; Hollander & Chappell, ; Sloane et al, ) and, whether or not social care was used (three studies, Table ) (Blackburn et al, ; Victor et al, ; Wysocki et al, ). The synthesis reports evidence according to these three sub‐groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One previous study investigated ambulance use for residential home residents with dementia and found a large number of calls related to trauma or an ambulatory care sensitive (ACS) condition (Amador et al . ).…”
Section: Discussionmentioning
confidence: 97%